2020
DOI: 10.3390/su12083403
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study on the Impact of Large-Scale Photovoltaic Development in Deserts on Local Air Temperature and Humidity

Abstract: As an important form of clean energy, photovoltaic (PV) power generation is entering a rapid development phase. Qinghai, China is located on the Qinghai-Tibet Plateau. It has sufficient sunlight and rich heat and light resources, includes a large area of the Gobi Desert, and has become China’s largest base for PV power generation. However, large-scale PV development in deserts changes the local surface energy distribution and impacts local microclimates. This study considered the Gonghe PV Power Plant in Qingh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Wu et al analyzed the temperature and humidity changes inside and outside the photovoltaic power plant under the Qinghai Gonghe desert. The results showed that the temperature change was small in the photovoltaic power plant during the day, and the temperature dropped sharply in the photovoltaic power plant at night; the relative humidity also increased in the station [8]. Armstrong et al [9] studied the difference in microclimate between the area under the photovoltaic array, the gap area, and the control area on a grassland with a solar array installed in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al analyzed the temperature and humidity changes inside and outside the photovoltaic power plant under the Qinghai Gonghe desert. The results showed that the temperature change was small in the photovoltaic power plant during the day, and the temperature dropped sharply in the photovoltaic power plant at night; the relative humidity also increased in the station [8]. Armstrong et al [9] studied the difference in microclimate between the area under the photovoltaic array, the gap area, and the control area on a grassland with a solar array installed in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been observed, that the construction and recent enlargement of the Gonghe Photovoltaic Power Plant have impacted the local climate, for instance, an increase in daytime temperatures and the nearby humidity, resulting in conditions favourable for vegetation build-up (Wu et al, 2020). This can result in a raised viscosity of sand grains to being less easily entrained by wind, potentially reducing the frequency of sandstorms (Wu et al, 2020). In addition, impacts of human infrastructure on former dune fields can be observed, when comparing satellite images prior to the construction of the Longyangxia reservoir in 1992 with images after.…”
Section: Discussionmentioning
confidence: 99%
“…Human influence is an important additional factor influencing dune morphology and dune migration. The GB was and is subject to major human influence on the dune landscape (Qi et al, 2021; Wu et al, 2020). The rising temperatures and precipitation have resulted in an increase of grassland converted to agriculture (Wang et al, 2018) and irrigated land (Yongnian et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…SP construction can also alter the aesthetic and ecological value of the land to affect human well‐being (Torres‐Sibille et al, 2009) and impact religious and cultural services for resident indigenous peoples (Grodsky & Hernandez, 2020; Mulvaney, 2017). After construction, the operation of SPs in dry climates can result in reduced albedo (Broadbent et al, 2019; Yang et al, 2017) and an increase in day‐ and night‐time temperatures (Barron‐Gafford et al, 2016; Wu et al, 2020), with implications for climate regulation in often heat‐stressed desert environments. Moreover, declines in photosynthetically active radiation under PV panels (Barron‐Gafford et al, 2019; Liu et al, 2019; Tanner et al, 2020) can modify plant community composition (Tanner et al, 2014) and promote invasive species (Tanner et al, 2020).…”
Section: Effects Of Solar Parks On Natural Capital and Ecosystem Serv...mentioning
confidence: 99%
“…Construction management practices informed by local hydrological and ecological inventories can protect ephemeral stream channels to preserve riparian habitats for desert wildlife (Grippo et al, 2015) and provide nesting or foraging opportunities for bird species (Rudman et al, 2017). During operation, PV panels can mitigate high soil temperatures (Barron‐Gafford et al, 2019; Tanner et al, 2020; Wu et al, 2020) and reduce soil evaporation (Liu et al, 2019). In hot arid regions, these changes can result in increased soil moisture and lead to greater diversity of wild plants (Tanner et al, 2020) and higher rates of seed bank survival (Hernandez et al, 2020), as well as enhance crop water use efficiency and total fruit production in agrivoltaic systems (Barron‐Gafford et al, 2019).…”
Section: Effects Of Solar Parks On Natural Capital and Ecosystem Serv...mentioning
confidence: 99%